Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

Mesoscale eddies in the Southern Ocean influence foraging trip behaviour of multiple penguin species - Joshua C. Wilson; Philip N. Trathan; Hugh J. Venables; David G. Ainley; Matthis Auger; Alistair M.M. Baylis; Charles-André Bost; Louise Emmerson; Kimberley T. Goetz; Mark A. Hindell; Jefferson T. Hinke; Catharine Horswill; et al. (Progress in Oceanography, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Habitat Use, Residency, and Connectivity of Bull Sharks (Carcharhinus leucas) in the Bazaruto Seascape, Mozambique - Stephanie K. Venables; Lukas Müller; Christoph A. Rohner; Andrea D. Marshall; Jimmy van Rijn; Nilza de Catarina; John D. Filmalter; Ryan Daly (Fishes, 2026)
Bull sharks (Carcharhinus leucas) are highly mobile coastal predators, whose broad movements complicate conservation planning, particularly in the Western Indian Ocean, where key habitats remain poorly understood. Using passive acoustic telemetry, this study assessed the habitat use, residency, and regional connectivity of adult bull sharks within the Bazaruto Seascape, Mozambique, evaluating the area’s ecological role within a wider movement network. Sharks tagged around Bazaruto exhibited high residency (overall Rmax = 0.45) and year-round presence, with core habitat concentrated along seaward reef systems and inshore areas off the San Sebastian Peninsula. Although most core habitat areas (82%) overlapped with existing marine protected areas, important habitats extended beyond protected area boundaries. In addition to supporting resident individuals, the seascape functioned as a seasonal waypoint within a regional movement corridor, with transient sharks exhibiting short periods (

Breaking barriers: Transoceanic movement by a bull shark - Ryan Daly; Taryn S. Murray; Michael J. Roberts; David S. Schoeman; Nicolas Lubitz; Adam Barnett; Riaan Cedras; Dunsin A. Bolaji; Grant M. Brokensha; Pamela M. Le Noury; Fabien Forget; Stephanie K. Venables (Ecology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Reported prevalence and quantitative LC-MS methods for the analysis of veterinary drug residues in honey: a review - Ryan Venable; Carion Haynes; Jo Marie Cook (Food Additives & Contaminants: Part A, 2014)